1994
DOI: 10.1007/bf00024026
|View full text |Cite
|
Sign up to set email alerts
|

Stability of bacterial leaf spot resistance in peach regenerants under in vitro, greenhouse and field conditions

Abstract: Phenotypic stability of bacterial leaf spot resistance in peach (Prunus persica (L.) Batsch) regenerants, either selected at the cellular level for insensitivity to a toxic culture filtrate of Xanthomonas campestris pv . pruni or screened at the whole plant level for resistance to X. campestris pv. pruni, was investigated. A detached-leaf bioassay was used to evaluate the original regenerants again after three years in the greenhouse and also after a two to three year cycle of tissue culture propagation . Peac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The reduction or instability of the somaclonal variation in the seed generation is less of a problem with perennials that rely on vegetative propagation for multiplication. Here the incidence of disease resistance in somaclones has been very encouraging (Ostry & Skilling, 1988;Prakash & Thielges, 1989;Hammerschlag et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction or instability of the somaclonal variation in the seed generation is less of a problem with perennials that rely on vegetative propagation for multiplication. Here the incidence of disease resistance in somaclones has been very encouraging (Ostry & Skilling, 1988;Prakash & Thielges, 1989;Hammerschlag et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…lycopersici was achieved by exposing tomato protoclones in vitro to a nonspecific toxin (Shahin & Spivey, 1986). Somaclones of peach selected in vitro were also found to show increased resistance to bacterial leaf spot (Hammerschlag et al, 1994) and somaclones of celery selected in vitro showed heritable resistance to Fusarium oxysporum f.sp. apii (Heath-Pagliuso et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Hammerschlag (1990) reported that 33-100% of peach regenerants (maintained under greenhouse conditions, but leaves assayed in vitro) were either significantly more resistant or susceptible to Xanthomonas campestris pv. pruni compared with the parent cultivar; however, only one regenerant retained increased levels of disease resistance under field conditions and had heritable resistance (Hammerschlag et al, 1994;Hammerschlag, 2000). In the present study, 15-21 regenerants per cultivar were evaluated, and the percentage of somaclonal variants with significantly higher levels of resistance to C. acutatum ranged from 25% for cultivar Honeoye to 100% for cultivars Chandler and Delmarvel (Table 1).…”
Section: Inoculation Evaluations For Strawberry Adventitious Shoot Rementioning
confidence: 97%
“…These same observations were reported for peach in response to X. campestris pv. pruni (Hammerschlag et al, 1994).…”
Section: Inoculation Evaluations For Strawberry Adventitious Shoot Rementioning
confidence: 99%
See 1 more Smart Citation